Experimental investigation of thin sheet formability during laser shock forming - Dong, Anna Siling (2013)
The increasing demand in the fabrication of micro systems has highlighted the significance of micro forming processes. However, existing micro forming techniques has limitations whereby a new metal forming process for sheet metals is developed and introduced in this project.